Grazing trajectory statistics and visualization platform based on cloud GIS - Dong Li; Chuanjian Wang; Qilei Wang; Tianying Yan; Wanlong Bing; Ju Wang (Journal of Cloud Computing: Advances, Systems and Applications, 2020)
Abstract It is very important for ranchers and grassland livestock management departments to master the information on the trajectory and feeding behavior of the herd timely and accurately. Therefore, this study developed a statistics and visualization platform for grazing trajectory. The platform was implemented by using the Web AppBuilder for ArcGIS framework and ArcGIS Online server. In particular, the trajectory processing service on the server was used to calculate walking speed, walking trajectory and feed intake of the herd in the platform. And these results were published to the ArcGIS Online server. The relevant information was analyzed and displayed by Web AppBuilder for ArcGIS calling the data on ArcGIS Online. Moreover, the paltform provided some visualization functions to support the visualization of user-defined analysis results. When users use the functions of spatial analysis (such as buffer analysis, finding hot pots analysis and interpolation point analysis), they can choose to analyze spatial data and related field information to conduct customized spatial data analysis. In a short, the platform realized the visualization functions of feed intake statistics, walking speed statistics, spatial analysis, line chart analysis and pie chart analysis of spatial data related attributes. It can provide technical support and data support for the relevant management departments to monitor grazing information and study the living habits of the herd.